Green product as a means of expressing green behaviour: A cross-cultural empirical evidence from Malaysia and Nigeria - Ogiemwonyi O.; Harun A.B.; Alam M.N.; Karim A.M.; Tabash M.I.; Hossain M.I.; Aziz S.; Abbasi B.A.; Ojuolape M.A. (Elsevier B.V., 2023)
Due to overconsumption, there is no significant urgency than the climate emergency for the publicity of green products that may conceivably led to reducing environmental impact. Considering the limited studies as a means of comparing green behaviour and its determinant in developing nations, this study focused on environmental awareness, attitude and perceived behavioural control (PBC) by applying the measurement of impacts on green behaviour. It further examined the role of green culture as a contributor. A total of 280 responses from Kuala-Lumpur, Malaysia and 267 responses from Abuja, Nigeria were obtained via questionnaire distribution among citizens (age 1832). SmartPLS3.0 and SPSS v22.0 were applied for statistical analyses. To request responses that we could not have anticipated, we utilized an open-ended format, accompanied by closed-ended format so we could compare the responses of the two sets samples. In both sets, we found 13% and 8% purchases organic food and energy-saving products in Malaysia while 24% and 8% purchases the same categories of products in Nigeria. We also found 40% of consumers in Malaysia purchased green products because of environmental benefit while 54% of consumers in Nigeria purchased green products because of health benefits. The path analyses result shows that attitude and green culture had a higher influenced on green behaviour in both nations. However, the propensity of green behaviour does not depend on economic development, for the reason that Nigeria had a higher mean value than Malaysia. PBC was found to be a contributor to Nigerian citizens with the least important for Malaysian citizens. Awareness interaction between green behaviour and green culture was insignificant for both country citizens. The study suggested that environmental education is important among citizens. Policy implications for these findings are further considered in the study. 2020 Elsevier B.V.